2009
DOI: 10.1111/j.1460-9592.2009.03074.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral metabolism during deep hypothermic circulatory arrest vs moderate hypothermic selective cerebral perfusion in a piglet model: a microdialysis study

Abstract: In this piglet model, both cerebral oxygenation and microdialysis findings suggested a depletion of cerebral energy stores during circulatory arrest in the DHCA18 group, compared to selective cerebral perfusion combined with circulatory arrest in the ASCP27 group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
9
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
5
9
1
Order By: Relevance
“…Multivariable analysis showed that MH was an independent protective factor against composite neurologic adverse events. These findings were in line with the consequence of a previous study and can be explained with the experimental consequence conducted by Cavus et al 10,17 No significant difference in neurological morbidity (either TND or PND) was observed between BACP and UACP (25 vs. 35.6%; p ¼ 0.687).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Multivariable analysis showed that MH was an independent protective factor against composite neurologic adverse events. These findings were in line with the consequence of a previous study and can be explained with the experimental consequence conducted by Cavus et al 10,17 No significant difference in neurological morbidity (either TND or PND) was observed between BACP and UACP (25 vs. 35.6%; p ¼ 0.687).…”
Section: Discussionsupporting
confidence: 92%
“…9 In an animal experiment, Cavus et al demonstrated that in the presence of ACP, there was a higher consumption of energy stores in the cerebral cells during CA and rewarming in DH than in MH. 10 Therefore, when CA was performed within a short duration, more composite benefits might be obtained from MH than DH.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] In the piglet model with DHCA, the level of lactate was observed to be persistently increased during the early stage after DHCA, whereas ASCP could attenuate this trend. [ 23 ] Consistently, jugular bulb pH was found to be significantly higher after ASCP comparing with DHCA[ 24 ] that is accordance with Hagl's et al . study, in which a lower pH could be observed even 4 h after DHCA, and ASCP could attenuate the acidosis.…”
Section: Discussionsupporting
confidence: 80%
“…Consequently, these results support the premise that stable and acceptable cerebral glucose levels might have a neuroprotective effect. Our results were consistent with those of Pokela et al ( 27 ) and Cavus et al ( 28 ) who posited that glucose is a marker with the most important predictive factors in postoperative death and cerebral function recovery.…”
Section: Discussionsupporting
confidence: 94%